Search for Diphoton Events with Large Missing Transverse Energy in 7 TeV Proton-Proton Collisions with the ATLAS Detector - Onofre, A. (2011)
A search for diphoton events with large missing transverse energy is presented. The data were collected with the ATLAS detector in proton-proton collisions at √s=7  TeV at the CERN Large Hadron Collider and correspond to an integrated luminosity of 3.1  pb−1. No excess of such events is observed above the standard model background prediction. In the context of a specific model with one universal extra dimension with compactification radius R and gravity-induced decays, values of 1/R<729  GeV are excluded at 95% C. L., providing the most sensitive limit on this model to date.